Previsão de falência: a percepção do empreendedor sobre a influência dos fatores não-financeiros - Silva, Fábio Braun (2011)
This paper had as main objective to identify “not financial factors” that could indicate a tendency of bankruptcy in small business, on based on perception of bankrupted businessman. This way, searched to identify how factors founded can matches influencing or not on risk of bankruptcy on organizations. So, the factors were analyzed on three different perspectives, searching to understand each factor separately. Throughout this paper, were studied factors related to entrepreneur, company and about environment. This way, intended with searched results to propose a group of recommendations for entrepreneurs with the objective of decrease bankruptcy risks on organizations.